Positron emission tomography (PET) in primary prostate cancer staging and risk assessment - Bednarova, Sandra; Lindenberg, Maria L.; Vinsensia, Maria; Zuiani, Chiara; Choyke, Peter L.; Turkbey, Baris (Translational andrology and urology, 2017)
Prostate cancer (PCa) is one of the few neoplasms that are not well served by 18F-Fluorodeoxyglucose (FDG) positron emission tomography (PET). As a result, a number of PET tracers have been developed to target particular biological features of PCa. Such agents can be used for diagnosis, staging, identification of biochemical recurrence (BCR) and evaluation of metastatic disease. Here, we focus on primary disease and local staging. To date, magnetic resonance imaging (MRI) has proven superior to PET in the imaging of primary PCa. However, some PET agents have shown remarkable promise in staging high-risk PCa (defined as any combination of a clinical T3, a PSA score >20 ng/mL, or a Gleason score of 8-10), as well as biochemical relapse after definitive therapy and metastatic PCa. PET agents can be divided into those that interrogate tumor metabolism ( 18 F-FDG, 11 C-Choline, 18 F-Choline, 11 C-Acetate, 18F-FACBC), hormone receptors (18F-FDHT), and other targets such as prostate specific membrane antigen (PSMA) ( 68 Ga-PSMA, 18 F-DCFBC, 18 F-DCFPyl) or gastric releasing peptide ( 18 F-GRP or 18 F-Bombesin). In this review, we compare the available PCa targeted PET tracers utilized in staging of high risk tumors.